A Study of High School Students Awareness towards Recycling Activity and Its Relationship with their Attitude and Behaviors related to Recycling Practices - Mohammad Asri, Asmaa; Daud, Zawawi (Recent Trends in Civil Engineering and Built Environment, 2021)
In 1998, the Ministry of Education of Malaysia had included Environmental Education into the school curricula of Malaysia. The objective of infusing Environmental Education in school was to provide environmental awareness, knowledge, attitude and behavior toward recycling activity among students. Although Environmental Education has successfully increased environmental awareness among students, it is not effective in changing the attitude and behavior of the students toward sustainable practice including recycling. The purpose of this study is to identify student awareness and identify the attitude and behavior among high school students of Sekolah Menengah Kebangsaan Pendang toward recycling practice. The survey was distributed to Form 1 to Form 5 students through some questionnaires which were selected according to the purpose of the study and the data collected from the respondent analyzed using the descriptive analysis method. The finding of this study shows that students have high awareness and good attitude towards recycling however student’s behavior toward recycling practice is still not satisfying. The study is expected to be a guide for schools, government and private sectors in coming up with effective strategies in order to provide better environmental education for the students according to student preferable ways.